Recent Advances in HTLV Research 2015 - Louis M. Mansky (MDPI - Multidisciplinary Digital Publishing Institute, 2017)
The human T-cell leukemia virus types 1 and 2 (HTLV-1 and HTLV-2) were both discovered over three decades ago and infect millions people worldwide. HTLV-1 is associated with the adult T-cell leukemia/lymphoma (ATLL) in about 2% of individuals infected, and another 2 to 3% of individuals develop a neurologic disorder called HTLV-associated myelopathy (HAM). HTLV-2 causes HAM in approximately 1 to 2% of infected individuals, but does not cause ATLL. HTLV-1 and HTLV-2 have served as excellent models for the study of the epidemiology and pathogenesis of virus-associated cancers as well as autoimmune conditions such as multiple sclerosis. Recently, two new members-HTLV-3 and HTLV-4-have been discovered in bushmeat hunters from central Africa, which emphasizes the urgent need for continual surveillance for new human retroviruses and their capacity to cause disease. Important public health issues remain open issues to be addressed in spite of the basic epidemiology of HTLV-1 and HTLV-2 being reasonably well defined. Clinical research is needed in developing potential HTLV-1 and HTLV-2 vaccines, as well as development of treatment options for ATLL and HAM. This 'Recent Advances Issue' contains both reviews and updates on research that encompasses these areas.